Need Analysis for Digital Supplement Book on the Collection of Megalithic Distribution Material in Pagar Alam City for History Learning in Senior High School - Seruni, Seruni; Syarifuddin, Syarifuddin; Chotimah, Umi; Della, Rhaptyalyani Herno; Suratmi, Suratmi (Teknodika, 2024)
This research aims to conduct a needs analysis for 3D pageflip-based digital supplement books on material from the collection of megalithic distribution in Pagar Alam City for history learning at SMA Negeri 1 Indralaya. Education requires the help of effective learning media to improve the quality of student learning outcomes. Students need technology-assisted learning media to make learning material easier to understand. Moreover, history learning really necessitates teaching materials that involve technology because they are considered interesting, effective, and interactive. At this stage, the researchers made observations and collected various data and information related to teaching materials in the form of digital supplement books. The research method employed to obtain data and information was a descriptive qualitative approach through questionnaires, interviews, and observations. The data analysis technique used was descriptive analysis with data reduction, data presentation, drawing conclusions, and verification. Based on a needs analysis questionnaire, data were obtained that 59.7% of students needed to study megalithic material, and 52.8% of students stated that it was very important to use digital learning media. Then, 95.8% of students were interested in learning using digital books, 45.8% of students answered that they were very interested in reading books if there were pictures contained in them, and 58.3% of students supported the development of innovations in history learning presented in digital book form at SMA Negeri 1 Indralaya. Therefore, to help improve the quality of learning, digital supplement books are an alternative.